2014
DOI: 10.1177/1071100714558511
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Perioperative Complications and Hospitalization Outcomes After Ankle Arthrodesis Versus Total Ankle Arthroplasty From 2002 to 2011

Abstract: Level III, comparative series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 14 publications
2
54
2
Order By: Relevance
“…This figure is fairly low compared with 1 TAA per 100,000 inhabitants in Sweden, Norway, and the United Kingdom [4, 5, 19], approximately 2 per 100,000 inhabitants in Finland and Germany [13, 20], 0.6 to 2.5 per 100,000 inhabitants in Australia and New Zealand [6, 21], and 1.9 to 4.0 per 100,000 inhabitants in the United States [3, 22]. The ratio of TAA to ankle arthrodesis was also low in the present study (1:6), compared with 1:2–3 in the United States, France, and Germany [3, 18, 20, 23]. These differences likely reflect preferences of surgeons in Japan to perform ankle arthrodesis over TAA compared with surgeons in Western countries.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…This figure is fairly low compared with 1 TAA per 100,000 inhabitants in Sweden, Norway, and the United Kingdom [4, 5, 19], approximately 2 per 100,000 inhabitants in Finland and Germany [13, 20], 0.6 to 2.5 per 100,000 inhabitants in Australia and New Zealand [6, 21], and 1.9 to 4.0 per 100,000 inhabitants in the United States [3, 22]. The ratio of TAA to ankle arthrodesis was also low in the present study (1:6), compared with 1:2–3 in the United States, France, and Germany [3, 18, 20, 23]. These differences likely reflect preferences of surgeons in Japan to perform ankle arthrodesis over TAA compared with surgeons in Western countries.…”
Section: Discussionmentioning
confidence: 50%
“…The blood transfusion rate was significantly lower in the ankle arthrodesis group. This result is contradictory to a report that compared the perioperative complications and hospitalization outcomes after ankle arthrodesis and TAA using the data of the National Inpatient Sample in the United States, which has been the only study comparing the blood transfusion rate between the two groups [23]. We could not perform a multivariate analysis to adjust for differences in demographics and comorbidities according to blood transfusion because of the small number of events.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…J.J. Jiang reported that TAR was independently associated with a lower risk of blood transfusion, non-home discharge, and overall complications when compared to ankle arthrodesis during the index hospitalization period. TAR was also independently associated with a higher hospitalization charge, but the length of stay was similar between the two groups [66]. S. Singer reported that improvement in patient-reported Ankle Osteoarthritis Scale and Short Form-36 scores were similar for both arthrodesis and TAR groups [24].…”
Section: Decision-making Process Of Using Arthrodesis or Tarmentioning
confidence: 96%
“…While these numbers are significantly lower than the number of procedures done for end-stage knee and hip arthritis (200 000 to 600 000), they are closer to the rates seen in shoulder arthritis where 24 000 complete arthroplasties were performed in 2010 in Medicare patients. 6,18,21,43 Historically, treatment of end-stage AA was an ankle arthrodesis, commonly referred to as ankle fusion (AF) procedure. This longstanding surgery was the preferred procedure for decades as initial trials of total ankle arthroplasty (TAA) in the 1970s had significantly high failure rates in first-and second-generation models.…”
mentioning
confidence: 99%